Microstructural Stability of Magnesium Alloys during High Temperature Deformation - Gao, Zhan (My University, 2009)
Superplastic forming (SPF) represents one feasible method to improve the formability of wrought magnesium alloy sheets at high temperatures. A fine grain structure not only improves the ductility but also increases the optimum strain rate thus, reducing the cost of SPF. Microstructural stability of AZ31 sheets have been characterized following different heat treatments. Second phase particles help to suppress grain growth due to the pinning effect. Thus once the temperature exceeds 450°C pmticles dissolve leading to abnormal grain growth. Superplastic behavior based on the fine grain structure of AZ31 was therefore evaluated at temperatures ranging from 200°C to 400°C with constant strain rates of 2.7*10-4 s-1 to 8.8*10-3 s-1. The dominant defonnation mechanism is grain boundary sliding, accommodated by dislocation creep. Under the current test conditions the initial (12μm grain size) structure is unstable and leads to dynamic recrystallization (DRX). Competition between DRX and grain growth leads to a variation of mechanical response with test conditions. Further grain refinement of AZ31 sheets was investigated through warm rolling tests for both symmetric and asymmetric types at 200°C and 300°C, followed by 200°C annealing. Asymmetric rolling was more effective for grain refinement and achieved better mechanical properties than symmetric rolling.
Keywords: Materials Science and Engineering; Materials Science and Engineering